Modulation of dendritic cell functions by viral IL-10 encoded by human cytomegalovirus - Avdic, Selmir; McSharry, Brian P.; Slobedman, Barry (Frontiers in Microbiology, 2014)
Human cytomegalovirus (HCMV), a clinically important β-herpesvirus, is a master of evasion and modulation of the host immune system, including inhibition of a number of dendritic cell (DC) functions. DCs play a central role in co-ordination of the immune response against pathogens and any disturbance of DC functions can result in a cascade effect on a range of immune cells. Recently, the HCMV gene UL111A, which encodes viral homologs of human interleukin 10, has been identified as a strong suppressor of a number of DC functions. In this mini review, we focus on HCMV encoded viral IL-10 mediated inhibitory effects on DCs and implications for the development of an effective HCMV vaccine.